Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif